(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2022)
In a vast experience of more than 55 years as an illuminator, the carioca Jorginho de Carvalho recognizes children’s theater as his first school. In this interview conducted in 2016, he discusses topics related to the creation of light for children and youth shows, socializing with the author and director Maria Clara Machado, beginning his career at the O Tablado school theater in Rio de Janeiro, in addition to the relationship with other important creators. for that specific audience. The conviviality and the experience of working with this illuminator aroused the need for an in-depth investigation of the psychological effects of light and a record of its possibilities in the children’s scenic universe that culminated in a doctoral project under development.